Efficient deprotection of phenol methoxymethyl ethers using a solid acid catalyst with Wells-Dawson structure - Romanelli, Gustavo Pablo (2001)
Deprotection of various phenols from their respective methoxymethyl ethers using an heteropolyacid catalyst was studied. The catalyst was the Wells-Dawson heteropolyacid, used both in bulk or supported on silica. Yields were high to quantitative after less than one hour reaction time and the catalyst was easily recoverable and reusable.